6=15u-9u

Simple and best practice solution for 6=15u-9u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=15u-9u equation:


Simplifying
6 = 15u + -9u

Combine like terms: 15u + -9u = 6u
6 = 6u

Solving
6 = 6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6u' to each side of the equation.
6 + -6u = 6u + -6u

Combine like terms: 6u + -6u = 0
6 + -6u = 0

Add '-6' to each side of the equation.
6 + -6 + -6u = 0 + -6

Combine like terms: 6 + -6 = 0
0 + -6u = 0 + -6
-6u = 0 + -6

Combine like terms: 0 + -6 = -6
-6u = -6

Divide each side by '-6'.
u = 1

Simplifying
u = 1

See similar equations:

| X+24=43.5 | | 4x+6y+3=17 | | 4x-7(x+3)=-36 | | 2.53-x=6.8 | | a-3=2.45 | | 16p/7=(2p-7)/4 | | y-4=-2/3 | | -12/x=3/4 | | 2x+33=3+7x-5 | | 9x-4=2x+12 | | 6y*y/6y | | B^2+4b=8 | | 6t^2+24t-100=0 | | 3x^3+4x^2+8x+6= | | 6x+6y=31.78 | | X^2+2x-99999=0 | | 6x+6y=31.95 | | X/5=36/4 | | x=sqrt(9x+63-3) | | 6n+10=19 | | 20x+25y=11700 | | 9(2-3x)-29=8x-(x-23) | | x=0.34x | | 5n+3=21 | | 3/7/8-1/5/8 | | P-11=39 | | 6.2=2.2+r | | 4-4x=5+6x | | 42-r=2 | | (2x)/(9-x^2)0 | | -0.5x+2.26=1.345 | | T+28=51 |

Equations solver categories